Addressing the Barriers to Trade and Investment in Nigeria from an Islamic Perspective - Muhammad, Adamu Abubakar; Abubakar Hussaini, Hamza; Adam Muhammad Ardo (Universitas Wahid Hasyim Semarang, 2024)
The objective of this research is to address the issue of trade and investment in Nigeria from an Islamic perspective. A comprehensive approach will be employed, encompassing the analysis of trade and investment policies, the identification of barriers and obstacles, and the consideration of Islamic teachings. This approach is designed to provide insights and solutions that will enhance trade and investment in Nigeria. The research methodology will entail a systematic and comprehensive literature analysis approach, encompassing the searching, collecting, and evaluation of literature sources relevant to the research topic. This process will be complemented by semi-structured interviews with relevant individuals. The overarching objective of this research endeavor is twofold: first, to contribute to Nigeria's economic advancement, and second, to promote societal inclusivity and prosperity. By meticulously examining Islamic principles and their implementation in the context of trade and investment, this study aims to offer a distinctive viewpoint and potential solutions to the challenges hindering trade and investment in Nigeria.